Osteoarthritis – a problematic skeletal trait in past human populations. Osteoarthritic changes vs. entheseal changes in the late medieval and early modern population form Łekno - Myszka, Anna; Piontek, Janusz; Tomczyk, Jacek; Zalewska, Marta (Anthropological Review, 2020)
According to medical knowledge, physical activity plays a role in osteoarthritic changes formation. The impact of occupation on osteoarthritic changes development in past human populations is not clear enough, causing problems with interpretation. The aim of the current study is to examine the relationship between osteoarthritis and entheseal changes. Skeletal material comes from the late medieval, early modern population from Łekno (Poland). The sample consists of 110 males and 56 females (adults only). Osteophytes, porosity and eburnation were analyzed in the shoulder, elbow, wrist, hip, knee, and ankle. Entheses on the humerus, radius, femur, and tibia were examined. Standard ranked categorical scoring systems were used for the osteoarthritic and entheseal changes examination. Males with more developed osteophytes in the shoulder have more “muscular” upper limbs (higher values of muscle markers). Males with more developed osteophytes in the hip and knee are predicted to have more “muscular” lower limbs. Males with more developed osteoarthritis in the shoulder, wrist, hip, and knee exhibit more developed entheseal changes. Males with more developed entheses tend to yield more developed osteophytes (all joints taken together) and general osteoarthritis (all changes and all joints taken together). Females with more developed entheses have more developed osteoarthritis in the elbow, wrist, and hip. Individuals with more developed entheses have much more developed osteophytes. When all the three types of changes are taken together, more “muscular” females exhibit more developed osteoarthritis. The lack of uniformity of the results, wild discussions on the usage of entheses in activity patterns reconstruction and other limitations do not allow to draw unambiguous conclusions about the impact of physical activity on the osteoarthritis in past populations and further studies are needed.